Sosialisasi Pengenalan Program Studi Pendidikan Fisika Kepada Siswa/Siswi di SMAN, SMKN, SMAS, dan SMKS Se-Kabupaten Mamasa - Andi Rosman N; Afiq Agung; Andi Saddia; Fauziah A; Fadhila Fadhila (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The socialization program is carried out to introduce the academic world to students. Higher Education is the final stage of formal education, commonly referred to as a university, institute, or academy. At this level, students are guided to specialize in a particular field of interest that will later become their foundation in the professional world. High school graduates generally aspire to secure a good career in the future, which creates intense competition among students across Indonesia to be admitted into top universities and their desired programs of study. The lack of knowledge about campus life is addressed through outreach or socialization activities, using methods such as presentations on the introduction to higher education followed by discussion sessions. This program aims to provide essential information to students, especially those in high school who plan to continue their education at the tertiary level. Through these activities, students can gain a clearer understanding of the university environment as a place where learning processes take place as well as where the mission and functions of higher education are realized. They are also introduced to campus ethics and regulations that must be observed. Furthermore, campus life includes interactions with various academic communities, including fellow students, lecturers, and administrative staff.